THE PORTFOLIO IN THE EVALUATION OF THE UNDERGRADUATE STUDENT IN THE HEALTH AREA: A BIBLIOMETRIC STUDY - Mariely Carmelina Bernardi; Marta Lenise do Prado; Silvana Silveira Kempfer; Kátia Regina Barros Ribeiro; Saionara Nunes de Oliveira (Cogitare Enfermagem, 2015)
This bibliometric study aimed to characterize Brazilian and international publications on the use of the portfolio in the evaluation of the undergraduate student in the area of health. Abstracts were selected of articles in Portuguese, English and Spanish, without using a filter for the year, from four databases and one virtual library, in June and July 2013. As a result, 167 articles were captured, from 1992 and 2013, the majority in English, originating from original research, from the United States, available on the Medical Literature Analysis and Retrieval System Online database and from the Nurse Education Today journal. The use of the portfolio is shown to be a current theme, being worked upon continuously and increasingly in various countries by researchers from distinct professional categories, a fact which is relevant to the transformation of education in the area of health and nursing.